Drying kinetics of tomato by using electric resistance and heat pump dryers - Queiroz, R.; Gabas, A. L.; Telis, VRN (Marcel Dekker Inc, 2004)
Drying kinetics of tomato was studied by using heat pump dryer (HPD) and electric resistance dryers with parallel and crossed airflow. The performance of both systems was evaluated and compared and the influence of temperature, air velocity, and tomato type on the drying kinetics was analyzed. The use of HPD showed to be adequate in the drying process of tomatoes, mainly in relation to the conversion rate of electric energy into thermal energy. The heat pump effective coefficient of performance (COPHT,EF) was between 2.56 and 2.68, with an energy economy of about 40% when compared to the drying system with electric resistance. The Page model could be used to predict drying time of tomato and statistical analysis showed that the model parameters were mainly affected by drying temperature.
Keywords: heat pump dryer; tomato; drying kinetics; COP; page model